Syringocystadenoma Papilliferum of Left Cheek in a 66 Year Old Adult - Bifica Sofia Lyngdoh; Thangjam Ruchika Devi; Bibenthung S Odyuo; Neizekhotuo Brian Shunyu; Sankappa P Sinhasan (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Syringocystadenoma papilliferum (SCAP) also known as papillary syringadenoma are rare tumors that are thought to arise from the apocrine or the eccrine sweat glands or both and occur usually in the head and neck region of children and adolescents. Hereby we report a case of a 66-year-old lady who presented with a 20-year history of a lesion on the left cheek. Despite the clinical appearance similar to basal cell carcinoma, histopathological examination identified it as Syringocystadenoma papilliferum. Since the tumor can undergo malignant transformation, complete excision is necessary.